Varroa destructor parasitism has a greater effect on proteome changes than the deformed wing virus and activates TGF-β signaling pathways - Erban, Tomas (Sci Rep, 2019)
Honeybee workers undergo metamorphosis in capped cells for approximately 13 days before adult emergence. During the same period, Varroa mites prick the defenseless host many times. We sought to identify proteome differences between emerging Varroa-parasitized and parasite-free honeybees showing the presence or absence of clinical signs of deformed wing virus (DWV) in the capped cells. A label-free proteomic analysis utilizing nanoLC coupled with an Orbitrap Fusion Tribrid mass spectrometer provided a quantitative comparison of 2316 protein hits. Redundancy analysis (RDA) showed that the combination of Varroa parasitism and DWV clinical signs caused proteome changes that occurred in the same direction as those of Varroa alone and were approximately two-fold higher. Furthermore, proteome changes associated with DWV signs alone were positioned above Varroa in the RDA. Multiple markers indicate that Varroa activates TGF-β-induced pathways to suppress wound healing and the immune response and that the collective action of stressors intensifies these effects. Furthermore, we indicate JAK/STAT hyperactivation, p53-BCL-6 feedback loop disruption, Wnt pathway activation, Wnt/Hippo crosstalk disruption, and NF-κB and JAK/STAT signaling conflict in the Varroa–honeybee–DWV interaction. These results illustrate the higher effect of Varroa than of DWV at the time of emergence. Markers for future research are provided.